Indian child with novel variant in OFD1 gene. Issue 10 (17th July 2020) - Panigrahi, Inusha; Ahuja, Chirag; Chaudhry, Chakshu
Abstract: Orofaciodigital syndrome (OFD) can have variable phenotype and presents with oral anomalies, facial dysmorphism, and digital malformations like syndactyly, and polydactyly. Other presentations also include renal and cardiac defects, and central nervous system anomalies like hydrocephalus and cerebellar abnormalities. OFD1 is a X‐linked dominant form of the syndrome presenting in females with mutations in CXorf5 or OFD1 gene. We describe a young child with sparse hairs, milia over face and absence of corpus callosum. Next generation sequencing showed frameshift pathogenic variant in the exon 13 of the OFD1 gene, consistent with diagnosis of OFD1.